SMART VIRTUAL PRODUCT DESIGN TO BOOST CONSUMER PRODUCT INDUSTRY 4.0 - Satya Ranjan Das (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This paper describes a method capable of improving the cycle of product production for manufactured industrial goods. The system is known as Smart Virtual Product Development (SVPD), and by using explicit knowledge of formal decision events, it helps in the decision making. It stores and reuses past decisive events or set of experiences related to various activities involved in the process of industrial product development, i.e. product design, manufacturing, and inspection. This system can potentially be used by large companies producing a range of similar products in mass production, or by a group of small and medium-sized enterprises (SMEs). This research explains how to enhance product manufacturing through the use of SVPD in Industry 4.0, where cyber-physical systems have to play the key role. Analysis of basic concepts and method of implementation shows that this is an expert system which facilitates the manufacture of products that can play a vital role towards Industry 4.0.